2011
DOI: 10.1128/cvi.00382-10
|View full text |Cite
|
Sign up to set email alerts
|

The Chimeric Protein Domain III-Capsid of Dengue Virus Serotype 2 (DEN-2) Successfully Boosts Neutralizing Antibodies Generated in Monkeys upon Infection with DEN-2

Abstract: Use of a heterologous prime-boost strategy based on a combination of nonreplicative immunogens and candidate attenuated virus vaccines against dengue virus in the same schedule is an attractive approach. These combinations may result in a condensed immunization regime for humans, thus reducing the number of doses with attenuated virus and the time spacing. The present work deals with the evaluation of the heterologous prime-boost strategy combining a novel chimeric protein (domain III-capsid) of dengue virus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The organization of DENV E protein dimers on the surface of the infectious virus has been modeled using crystal structures of DENV recombinant E (rE) and cryo-EM reconstructions of the virion (8,10,26,27). Furthermore, neutralizing mouse mAbs have been mapped extensively to the rE protein, and DENV subunit vaccines using the rE protein are currently being developed (11)(12)(13)(14)(15)(28)(29)(30). We next assessed whether epitopes targeted by neutralizing Abs in human immune sera were preserved on the rE protein.…”
Section: Resultsmentioning
confidence: 99%
“…The organization of DENV E protein dimers on the surface of the infectious virus has been modeled using crystal structures of DENV recombinant E (rE) and cryo-EM reconstructions of the virion (8,10,26,27). Furthermore, neutralizing mouse mAbs have been mapped extensively to the rE protein, and DENV subunit vaccines using the rE protein are currently being developed (11)(12)(13)(14)(15)(28)(29)(30). We next assessed whether epitopes targeted by neutralizing Abs in human immune sera were preserved on the rE protein.…”
Section: Resultsmentioning
confidence: 99%
“…Given the ability of anti-EDIII antibodies to contribute robustly to homologous protection with minimal cross-reactive binding, recombinant EDIII protein has been proposed as a vaccine candidate (Block et al, 2010; Valdes et al, 2009, 2011). In initial studies using a novel capsid-EDIII recombinant fusion protein, Valdes et al (2009) demonstrated a measurable humoral and cellular immune response; when the protein was used to boost a homologous infection, the antibody response was both potent and long-lasting (Valdes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In initial studies using a novel capsid-EDIII recombinant fusion protein, Valdes et al (2009) demonstrated a measurable humoral and cellular immune response; when the protein was used to boost a homologous infection, the antibody response was both potent and long-lasting (Valdes et al, 2011). In a separate set of experiments, Block et al (2010) tested a similar hypothesis using an insect cell-derived, recombinant EDIII-based protein vaccine and found that vaccination of mice with tetravalent EDIII protein produced antibodies that exhibited both neutralizing and enhancing activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the second approach, monkeys received a single s.c. dose of DV2 and were boosted three months later with 100 μg of EDIIIC (Valdés et al, 2011). Administration of the recombinant proteins eff ectively boosted the neutralizing antibody responses elicited with the virus (Valdés et al, 2010;Valdés et al, 2011). Th ese antibodies persisted at high levels (PRNT 50>300) for at least six months aft er the boost dose.…”
Section: Domain Iii-dengue Virus Capsid Proteinmentioning
confidence: 99%
“…In a fi rst approach, monkeys were primed with a single dose of DV2 and boosted fi ve months later with 300 μg of EDIII-P64k (Valdés et al, 2010). In the second approach, monkeys received a single s.c. dose of DV2 and were boosted three months later with 100 μg of EDIIIC (Valdés et al, 2011). Administration of the recombinant proteins eff ectively boosted the neutralizing antibody responses elicited with the virus (Valdés et al, 2010;Valdés et al, 2011).…”
Section: Domain Iii-dengue Virus Capsid Proteinmentioning
confidence: 99%